Study of Education Leverage Factors to Improve Sampang Human Development Index - Sahirul Alim, Helmy; Rohmah, Nurir; Milawati, Milawati (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
Education contributes to improving human quality, which is highly related to the development of a regency. In general, the HDI or IPM in Sampang Regency has increased, according to data from BPS, the Human Development Index (HDI) of Sampang Regency in 2022 reached 63.39, an increase of 0.59 points (0.94 percent) compared to the previous year's achievement (62.80). During 2010-2022, the HDI of Sampang Regency increased by an average of 1.36 per cent per year from 54.49 in 2010 to 63.39 in 2022. This study aims to analyze the IPM in Sampang in order to find out what leverage factors can be used as a basis for factors that can increase HDI in Sampang Regency. The Central Bureau of Statistics (BPS) only counts students who continue their studies in the Sampang Regency area as IPM data in the education sector. This problem makes the Expected Years of Schooling (HLS) numbers low in Sampang Regency. Meanwhile, the issue of Average Years of Schooling (RLS) will be expected to increase with the Paket C program. The results of this study are expected to be a reference for various parties who will analyze the Human Development Index (IPM) in the field of education. In particular, it is expected to be a reference for parties involved in the formulation of IPM in the field of education in Sampang Regency.